Meaningful Engagement Among Assisted Living Residents With Dementia: Successful Approaches. (December 2021) - Kemp, Candace L.; Bender, Alexis A.; Ciofi, Joy; Craft Morgan, Jennifer; Burgess, Elisabeth O.; Duong, Stephen; Epps, Fayron R.; Hill, Andrea Michelle; Manley, Pamela R.; Sease, Jasmine; Perkins, Molly M.
Meaningful engagement is an important dimension of quality of life and care for persons living with dementia, including the growing number who reside in assisted living communities. This report presents preliminary findings from an ongoing qualitative study aimed at identifying best care practices to create and maintain meaningful engagement among persons with dementia. Over a 1-year period, we conducted interviews, residents' record review, and participant observations in four diverse care communities. Our analysis identified four approaches that successfully promote meaningful engagement: (a) knowing the person, (b) connecting with and meeting people where they are, (c) being in the moment, and (d) viewing all encounters as opportunity. Incorporation of these approaches in care routines and adoption by all care partners can promote meaningful engagement, including during crises such as COVID-19.